Fear of Love Online: The Effect of Religious Salience on the Early Adoption of Online Dating (2000-2005) - Gurrentz, Benjamin Thomas (Interdisciplinary journal of research on religion, 2016)
From 2000 to 2005, online dating became a more viable option for mate selection and its usage boomed. The early adoption period of new technology (e.g., online dating) often is vital for new behavioral norms to spread, and it also provides an important historical context for examining how social groups respond differently to sudden changes in dating, marriage, and the family. This paper examines a specific social group that failed to adopt online dating during its early development: those who identify as very religious. Examining a nationally representative sample of Internet users who were single at some point from 2000 to 2005 (N=910), this study finds that those with high religious saliency were less likely to attempt online dating, despite its boom in popularity at the time. Mistrust of online dating websites partially explains this relationship, while religious attendance does not. This reflects a long history of very religious individuals resisting secular social changes to traditional patterns of dating, marriage, and the family. However, as religious individuals adapt and negotiate boundaries with secular culture over time, it is possible that online dating may become a more viable option for the very religious under certain conditions, which this article later discusses.